Elevation of serum N-terminal pro-brain natriuretic peptide after exercise is an index of myocardial damage or a cytoprotective reflection? - Faviou, E.; Zachari, A.; Nounopoulos, C.; Agrafiotis, E.; Vourli, G.; Dionyssiou-Asteriou, A. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. Recent investigations have suggested the occurrence of transient cardiac dysfunction and reversible myocardial injury in healthy individuals after heavy exercise. Our purpose was to examine if the release of N-terminal pro-brain natriuretic peptide (NT-proBNP) after intense exercise in obviously healthy participants may have cytoprotective and growth-regulating effects or may result from myocardial dysfunction/damage with changes in cTnT as a marker for myocardial cell necrosis during exercise. Methods. In 43 highly-trained male athletes <35 years old, who were examined immediately after exercising as well as 2 days later, 21 age-matched male patients classified as stage-B according to ACC/AHA guidelines and 35 healthy age-matched males, we evaluated NT-proBNP and 3rd generation's cTnT by electrochemiluminescence immunoassay. All participants underwent a detailed cardiac protocol including echocardiography and electrocardiogram (ECG). Results. In athletes, cTnT consistently remained <0.01 mg/L after exercising as well as after 2 days. NTproBNP immediately after exercising was 58.27±19.48 ng/L, without reaching pathological levels, decreasing 2 days later to 22.93±10.22 ng/L. Our patients maintained high levels of NTproBNP, as much as a six-fold increase with reference to the levels of our study's control group and with cTnT <0.01 mg/L. In the control group, cTnT and NTproBNP levels were statistically similar with those of the athletes 2 days after exercising. NT-proBNP as a biological marker can reliably discriminate pathological from physiological cardiac hypertrophy. Conclusion. A normal plasma concentration of NT-proBNP in consecutive routine check-up, before and after exercise, could minimize the possibility of cardiac dysfunction, whereas persistent elevated plasma concentrations warrant further cardiological evaluation.